THE ROLE OF REGIONAL MEDIA IN THE DEVELOPMENT OF SOLUTIONS JOURNALISM IN UZBEKISTAN (TAMADDUN NURI JURNALI, 2024)
This article analyzes the emergence of Internet journalism and the necessity for a new direction—solutions journalism—addressing social issues and forming evidence-based comprehensive responses, using examples from leading electronic publications in the Khorezm region.